p66Shc deficiency in CLL cells enhances PD-L1 expression and suppresses immune synapse formation - Lopresti, Ludovica; Capitani, Nagaja; Tatangelo, Vanessa; Tangredi, Carmela; Boncompagni, Gioia; Frezzato, Federica; Visentin, Andrea; Marotta, Giuseppe; Ciofini, Sara; Gozzetti, Alessandro; Bocchia, Monica; Trentin, Livio; et al. (Frontiers in Cell and Developmental Biology, 2024)
Introduction: Escape from immunosurveillance is a hallmark of chronic lymphocytic leukemia (CLL) cells. In the protective niche of lymphoid organs, leukemic cells suppress the ability of T lymphocytes to form the immune synapse (IS), thereby hampering T-cell mediated anti-tumoral activities. By binding its cognate receptor PD-1 at the surface of T lymphocytes, the inhibitory ligand PD-L1, which is overexpressed in CLL cells, mediates the T-cell suppressive activities of CLL cells. However, the molecular mechanism underlying PD-L1 overexpression in CLL cells remains unknown. We have previously reported a defective expression of the pro-apoptotic and pro-oxidant adaptor p66Shc in CLL cells, which is causally related to an impairment in intracellular reactive oxygen species (ROS) production and to the activation of the ROS-sensitive transcription factor NF-κB. The fact that PD-L1 expression is regulated by NF-κB suggests a mechanistic relationship between p66Shc deficiency and PD-L1 overexpression in CLL cells. Methods: 62 treatment-naive CLL patients and 43 healthy donors were included in this study. PD-L1 and p66Shc expression was quantified in B cells by flow cytometry and qRT-PCR. IS architecture and local signaling was assessed by flow cytometry and confocal microscopy. CD8+ cell killing activity was assessed by flow cytometry. Results: Here we show that residual p66Shc expression in leukemic cells isolated both from CLL patients and from the CLL mouse model Eμ-TCL1 inversely correlated with PD-L1 expression. We also show that the PD-L1 increase prevented leukemic cells from forming ISs with T lymphocytes. Reconstitution of p66Shc, but not of a ROS-defective mutant, in both CLL cells and the CLL-derived cell line MEC-1, enhanced intracellular ROS and decreased PD-L1 expression. Similar results were obtained following treatment of CLL cells with H2O2 as exogenous source of ROS, that normalized PD-L1 expression and recovered IS formation. Discussion: Our data provide direct evidence that the p66Shc-deficiency-related ROS depletion in CLL cells concurs to enhance PD-L1 expression and provides a mechanistic basis for the suppression of T cell-mediated anti-tumoral functions in the immunosuppressive lymphoid niche.